Fertilización orgánica de dos variedades de plátano (Musa AAB) en un suelo ácido de la Banda de Shilcayo - región San Martín - Ushiñahua Rojas, Juan Carlos (2006)
This research was llev6 out during the period January 2003 to March 2004, at the Experimental Station of Tropical Crops Institute, located 2.5 km. From Tarapoto, district Shilcayo province and department of San Martin; in order to determine the effect of chicken manure and chemical formulation (NPK) on yield banana variety "lnguiri" and "Vellaco" and its cost / benefit ratio in acid soils of San Martin. The experimental soil at the beginning the experiment presented extremely acidic reaction (pH = 4.0}, texture class! sandy clay loam, low levels of nitrogen, phosphorus and potassium. The factors studied were composed of varieties of banana (a1 = Bellaco and 32 = lnguiri) and levels of chicken manure (b1 = O th / a, b2 = 5 t / ha, b3 = 10 t / ha and b4 = 15 t /he has). The experimental design used was Randomized complete block factorial arrangement 2A x 48, plus two additional witnesses (inorganic fertilization in the two varieties of banana) with three blocks or replicates per treatment. The results indicate a better effect of the application of chicken manure on plant height, girth of pseudostem, number of leaves, number of tillers / matte, earliness to flowering and harvesting bananas in relation to inorganic fertilization and non-application chicken manure (b1 = O t / ha). Likewise, similar behavior of organic fertilization on productive characteristics such as number of fingers per bunch, bunch weight (kg) and performance (tlha) is observed; achieving a better effect in the two varieties under study when applying b3 level (10 t / ha), with an average yield of 16.56 and 23.72 t / ha of banana variety "Bellaco" and "lnguiri, respectively. On average, using the b3 level (10 t / ha of chicken manure), an 56.2% increase in performance in relation to the non-application of chicken manure (b1 " 'O t / ha) was observed, whereas the effect of inorganic fertilization was only 7.30% higher than the cost / benefit ratio, and tends to increase as yields increase, with the greatest ratio in the range "lnguiri" by applying 10 t / ha of chicken manure with 1.53.; while the variety "knave" older relations is observed by applying 5 to 10 t / ha of chicken manure with 1.19y1.18, respectively